Pengaruh Dewan Komisaris Independen, Komite Audit, dan Kepemilikan Asing Terhadap Green banking Disclosure (Studi Pada Perbankan Di Indonesia Tahun 2017-2021) - Aulia Rahmiati; Henri Agustin (Wahana Riset Akuntansi, 2022)
The purpose of this study was to examine the impact of independent commissioners, audit committees, and foreign ownership on the green banking disclosures of Indonesian banks in 2017-2021. The population in this study is banking in Indonesia in 2017-2021 and the sample in this study is 35 banks. The sample in this study was obtained by using purposive sampling method. The method used to assess green banking practices is using content analysis that refers to green banking disclosure indicators. Causality relationship between independent board of commissioners, audit committee, and foreign ownership and disclosure of green banking was tested using multiple linear regression analysis method. This study found that there was a significant effect between the audit committee on green banking disclosure practices in Indonesian banks and did not find any influence between independent commissioners and foreign ownership on green banking disclosure practices.Keyword: Independent Commissioners, Audit Committees, Foreign Ownership, Green banking